2019
DOI: 10.1016/j.bbadis.2019.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin exerts protective effects similar to bexarotene in Alzheimer's disease by modulating amyloid-beta and cholesterol homeostasis in blood-brain barrier endothelial cells

Abstract: Click here to view linked References HIGHLIGHTS 1) Asx exerts beneficial effects similar to Bex in brain capillary endothelial cells 2) non-amyloidogenic APP processing is enhanced via BACE1 and ADAM10 modulation 3) ABCA1 is upregulated and cellular cholesterol efflux is stimulated involving nuclear receptor-dependent mechanisms 4) LRP-1 is up regulated along with augmented Aβ uptake/transcytosis 5) Silencing of LRP-1 or inhibition of ABCA1 reverses effects of Asx and Bex on APP processing/Aß species 6) Asx an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 106 publications
2
33
0
Order By: Relevance
“…The present results indicated that astaxanthin decreased Ab42 deposition and prevented memory decline in the App NL-G-F mice. Consistently, two recent studies reported that astaxanthin reduced Ab40 levels in a 3xTg AD mouse model (Fanaee-Danesh et al, 2019) and reduced Ab42 levels in rats with intracerebroventricular injections of Ab42 (Rahman et al, 2019). The present study further indicated that astaxanthin decreased pTau and the Iba1 fraction, while it increased hippocampal PV-positive neuron density and total GSH levels.…”
Section: Protective Mechanisms Of Astaxanthinsupporting
confidence: 91%
“…The present results indicated that astaxanthin decreased Ab42 deposition and prevented memory decline in the App NL-G-F mice. Consistently, two recent studies reported that astaxanthin reduced Ab40 levels in a 3xTg AD mouse model (Fanaee-Danesh et al, 2019) and reduced Ab42 levels in rats with intracerebroventricular injections of Ab42 (Rahman et al, 2019). The present study further indicated that astaxanthin decreased pTau and the Iba1 fraction, while it increased hippocampal PV-positive neuron density and total GSH levels.…”
Section: Protective Mechanisms Of Astaxanthinsupporting
confidence: 91%
“…At 10 nM, AST was found to double the mRNA expression of ADAM10 in primary porcine brain capillary endothelial cells [132]. Moreover, AST, presumably via PPARα agonism, also increased endothelial expression of lipoprotein receptor-related protein 1 (LRP1), a protein expressed on the abluminal surface of brain capillaries that functions to transport amyloid β monomers and oligomers from the brain [132,133]. Importantly, genetic knockout of LRP1 in 5XFAD AD model mice elevates their brain levels of soluble amyloid β and exacerbates their cognitive dysfunction [133].…”
Section: Controlling Amyloid β Production Via Modulation Of Bace1 and Adam10 Expressionmentioning
confidence: 95%
“…Remarkably, AST can act as a PPARα agonist in physiologically relevant low nanomolar concentrations [130,131]. At 10 nM, AST was found to double the mRNA expression of ADAM10 in primary porcine brain capillary endothelial cells [132]. Moreover, AST, presumably via PPARα agonism, also increased endothelial expression of lipoprotein receptor-related protein 1 (LRP1), a protein expressed on the abluminal surface of brain capillaries that functions to transport amyloid β monomers and oligomers from the brain [132,133].…”
Section: Controlling Amyloid β Production Via Modulation Of Bace1 and Adam10 Expressionmentioning
confidence: 99%
“…Similarly, the effect of the peroxisome proliferator‐activated receptor α agonist, astaxanthin on cellular cholesterol metabolism, APP processing/production has been demonstrated with the help of 3xTg AD mice. This study revealed that astaxanthin can reduce BACE1 and increase LRP‐1 expression in 3xTgAD mice brain (Fanaee‐Danesh et al., 2019).…”
Section: Introduction To Oxysterolsmentioning
confidence: 89%